Mary ebook An awakening of terror. - Cassidy, Nat (Tor Nightfire, 2022)
Nat Cassidy's highly commercial, debut horror novel Mary: An Awakening of Terror , blends Midsommar with elements of American Psycho and a pinch of I'll Be Gone in the Dark . Best Horror of 2022— Esquire, Paste Magazine, CrimeRead Harper's Bazaar 15 Best Books for Spooky Season The Lineup Best Debut Horror Novels of 2022 American Writers Museum—Staff Recommendation Mary is a quiet, middle-aged woman doing her best to blend into the background. Unremarkable. Invisible. Unknown even to herself. But lately, things have been changing inside Mary. Along with the hot flashes and body aches, she can't look in a mirror without passing out, and the voices in her head have been urging her to do unspeakable things. Fired from her job in New York, she moves back to her hometown, hoping to reconnect with her past and inner self. Instead, visions of terrifying, mutilated specters overwhelm her with increasing regularity and she begins auto-writing strange thoughts and phrases. Mary discovers that these experiences are echoes of an infamous serial killer. Then the killings begin again. Mary's definitely going to find herself. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.